PENGARUH IMPLEMENTASI BIG DATA ANALYTICS TERHADAP KUALITAS AUDIT PADA BADAN PEMERIKSA KEUANGAN NEGARA REPUBLIK INDONESIA - Muhammad Fahri Rizky Saputra (2023)
This research is a quantitative study that aims to determine the effect of perceived usefulness in implementing Big Data Analytics on audit quality at audit board of the Republic of Indonesia (BPK RI). This research uses BPK RI auditors as the research sample. Selection of the sample using purposive sampling technique, with predetermined criteria. Testing the hypothesis in this study using SEM analysis with SmartPLS 3.2.9 software and a significance level of 5% (0,05). The results if this test show that perceived usefulness in implementing Big Data Analytics has a significant effect on audit quality, while perceived use in implementing Big Data Analytics does not have a significant effect on audit quality.